Strength of weak ties: Network, intermediary and Governance in Sonitpur District of Assam - PRIYANKUHAZARIKA, (International Journal of Psychosocial Rehabilitation, 2020)
Society where commodities and services are not equitably distributed, people have little choice(s) but to opt for informal ways to communicate their necessities and urgencies to the concerned authorities or department of the government. To available their exigencies, many communities, owing to desperation look to bypass any bureaucratic protractions. As a result, it entails linkages and seeking help of the intermediaries toprocure the entitlements and government schemes. In most parts of the country such informal connections with the authorities in primary strata of governance i.e Gram Panchayat office become inevitable for the people to avail any government aides and entitlements. These includes: PDS, housing, and maternity benefit schemes, too. This informal association gradually translates into a nexus closely knitted around religion, ethnicity or community allegiance. Even though petty corruption results payment to the intermediaries (dalaal); naïve villagers are willing to have accesses to various welfare services both in the government offices and the PRI’S. The present study is committed to analyze specific ways, means and mechanism that people adopts to reach out to the immediate institutions of governance at the local level in their everyday life. To procure primary data for an authentic field based study, the people of Sonitpur district of Assam is referred to as the primary source of quantitative reference, here. The study tries to examine the everyday form of transaction between the state and its subjects. The role and influence of such informal association in the exercise of the interaction between the state and its people, role of intermediaries and bio politics of the post-modern state in terms of governance and administration are duly paid attention. The study tries to understand these states of affairs in the context of diurnal occupations of the two government offices of the Sonitpur district